«MY RELATIONSHIPS WITH DRAHOMANOV WERE PRETTY INTERESTING» (NATALIA KOBRYNSKA AND MYKHAYLO DRAHOMANOV: VECTORS OF LIFE AND CREATIVITY) - Швець, А. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article on the base of memoirs and epistolary material it is overviewed Mykhaylo Drahomanov’s and Natalia Kobrynska’s relationships of life and creativity. The character of Drahomanov’ sinfluenceon Kobrynska’s formation of national consciousness and ideological Europeanism is understood. Attention is paid to certain ideological differences between them in the women’s issue, the concept of radicals and the publishing representation of the women’s movement. For Kobrynska herself, this acquaintance had a decisive influence, both in terms of her generational integration, and from the point of view of Drahomanov’s authoritative support for her feminist activity.